Between Foucault and Derrida - Aryal, Yubraj; Cisney, Vernon W.; Morar, Nicolae, 1979-; Penfield, Christopher (Edinburgh University Press, 2016)
Explores the biographical, historical and philosophical connections between Jacques Derrida and Michel Foucault. Between Foucault and Derrida explores the notorious Cogito debate and includes: the central articles, an important piece by Jean-Marie Beyssade, along with a letter Foucault wrote to Beyssade in response - both these pieces available for the first time in English translation. In the second part of the book, 10 essays written by some of the most well-known scholars working in contemporary continental philosophy address the various philosophical intersections and divergences of these two profoundly important thinkers. Key Features. The first collection of the central essays involved in the Cogito debate between Foucault and Derrida Includes the first English translations of Jean-Marie Beyssade's important 1973 article on the debate and Foucault's letter in response Some of the best-known scholars working in continental philosophy today examine where Foucault and Derrida converge and diverge, and how they ultimately shaped each other's projects Contributors. Amy Allen, Penn State University, Pennsylvania, USA. Ellen Armour, Vanderbilt Divinity School, Tennessee, USA. Yubraj Aryal, University of Montreal, Canada and New York University, USA. Jean-Marie Beyssade, University of Paris IV, France. Vernon W. Cisney, Gettysburg College, Pennsylvania, USA. Fred Evans, Duquesne University, Pennsylvania, USA. Peter Gratton, Memorial University of Newfoundland, Canada. Leonard Lawlor, Penn State University, Pennsylvania, USA. Edward McGushin, Stonehill College, Massachusetts, USA. Nicolae Morar, University of Oregon, Oregon, USA. Jeff Nealon, Penn State University, Pennsylvania, USA. Christopher Penfield, Purdue University, Indiana, USA. Arkady Plotnitsky, Purdue University, Indiana, USA. Paul Rekret, Richmond, The American International University in London, UK. Alan Schrift, Grinnell College, Iowa, USA. Derrida and Foucault are unquestionably two of the most influential philosophers of the 20th century. Both share a similar motivation to challenge our fundamental structures of meaning - in texts, political structures, and epistemic and discursive practices - in order to inspire new ways of thinking. Between Foucault and Derrida explores the notorious Cogito debate and includes: the central articles, an important piece by Jean-Marie Beyssade, along with a letter Foucault wrote to Beyssade in response - both these pieces available for the first time in English translation. In the second part of the book, 10 essays written by some of the most well-known scholars working in contemporary continental philosophy address the various philosophical intersections and divergences of these two profoundly important thinkers.